Assessment of Association Between the Potential Immunomodulatory Activity and Drinking Olive Leaf Tea in the Coronavirus Disease-2019 Pandemic: An Observational Study - Kocyigit, Abdurrahim; Guler, Eray Metin; Irban, Arzu; Kiran, Bayram; Atayoglu, Ali Timucin (Mary Ann Liebert Inc, 2022)
Objective: During the Coronavirus Disease-2019 (COVID-19) pandemic, in addition to the current measures, the healthy immune system plays an essential role and various natural agents have been recommended to boost innate immunity. The aim of this study was to investigate any association between the potential immunomodulatory activity and drinking olive leaf tea (OLT) in the COVID-19 pandemic. Design: The study was conducted among the workers in a tractor factory where OLT was served in routine. Drinking at least one cup of OLT per day for a minimum of 1 month was the inclusion criteria used in the study. The workers who had a history of vaccination and COVID-19 were excluded from the study, and lymphocyte subsets, interleukin (IL)-2, IFN-γ, COVID-19-specific IgM and IgG levels were analyzed in all the participants to determine the asymptomatic individuals among the participants and compare the immunological parameters. Results: The study was conducted among 336 workers, 183 of them were OLT drinkers and 153 were OLT nondrinkers. The results showed higher values of CD3-/CD16/56 (natural killer [NK]) cells, CD3+/CD16/56 (natural killer T [NKT]) cells, total NK (NK+NKT) cells, and serum IFN-γ, and IL-2 levels in OLT drinkers compared to the nondrinkers. Although all the OLT drinkers and nondrinkers included in the study reported no history of COVID-19, specific COVID-19 IgG levels were found positive in 60% of OLT drinkers and 38% OLT nondrinkers. Conclusions: Peripheral NK and NKT cell values and IL-2 and IFN-γ secretion levels were found higher in the OLT drinking group. There were positive correlations between the OLT drinking frequency and NK cell counts. Moreover, the number of individuals who had "asymptomatic" COVID-19 infection was higher in the OLT drinking group than in the nondrinking cohort. Clinical Trial Registration Number: The trial has been registered in the ClinicalTrials.gov database (CTR NCT05222347).
Keywords: Prevention; Olive Leaf Tea; COVID-19; An Observational Study.-, Journal of integrative and complementary medicine, 2022 [Kocyigit A., Guler E. M. , Irban A., Kiran B., Atayoglu A. T. , -Assessment of Association Between the Potential Immunomodulatory Activity and Drinking Olive Leaf Tea in the Coronavirus Disease-2019 Pandemic]; Natural Killer Cells; Plant Leaves; Immunomodulating Agents; Immune System; Immunoglobulin G; Olea; Humans; Interleukin-2; Pandemics; Teas, Herbal; 3. Good health